GIGYF2: A Multifunctional Regulator at the Crossroads of Gene Expression, mRNA Surveillance, and Human Disease - Chen-Shuo Zhao; Shu-Han Liu; Zheng-Yang Li; Jia-Yue Chen; Xiang-Yang Xiong (Cells)
GIGYF2 (Grb10-interacting GYF protein 2) functions as a versatile adaptor protein that regulates gene expression at various levels. At the transcriptional level, GIGYF2 facilitates VCP/p97-mediated extraction of ubiquitylated Rpb1 from stalled RNA polymerase II complexes during DNA damage response. In mRNA surveillance, GIGYF2 participates in ribosome collision-induced quality control, nonsense-mediated decay, no-go decay, and non-stop decay pathways. Furthermore, GIGYF2 interacts with key factors including 4EHP, TTP, CCR4-NOT, DDX6, ZNF598, and TNRC6A to mediate translational repression and mRNA degradation. Additionally, dysregulation of GIGYF2 has been implicated in various pathological conditions, including metabolic diseases, vascular aging, viral infections, and neurodegenerative disorders. This review summarizes the structural and functional characteristics of GIGYF2, highlighting its importance in transcriptional regulation, mRNA surveillance, translational inhibition, and mRNA degradation, while also elucidating its potential as a therapeutic target for disease treatment.